The Development of 2P2M Learning Tools for Students with Cognitive Style Reviews in Differential Calculus Courses - Fitriana Eka Chandra (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2017)
This research describes the development of learning tools with Mind Mapping Problem Posing for students with cognitive style of field dependent and fied independent. Learning tools made in the form of syllabus, RPP, and LKM. There are two types of LKM developed, LKM for students who have an independent field cognitive style and who have a cognitive field dependent style. Of course, before the learning takes place required a cognitive style test first for students. The cognitive style test to determine the type of cognitive style that each student has. This research is a development research with the development model used is Thiagarajan development model known as Four-D Models (Model 4D). After analyzed, the learning tools can be applied in the learning in the classroom.Keywords: problem posing, mind mapping, cognitive style, learning tool, calculus